Menavigasi Daya Saing dan Determinan Ekspor Unggulan Indonesia di Kawasan Carribean Community (Caricom): Navigating Products Competitiveness and Determining Indonesia's Leading Exports in the Caribbean Community (CARICOM) Region - Hotsawadi; Widyastutik (National Research and Innovation Agency, 2023)
CARICOM is an area that has trade potential to be explored by Indonesia. However, for Indonesia, this region has various challenges to explore considering that the countries that are members of it are non-traditional countries. For this reason, this study aims to analyze the competitiveness, competitor countries and determinants of exports of Indonesia's superior products to the CARICOM region. The analysis methods used are market share, RCA, EPD, X-Model and panel data regression. The results showed that ten commodities identified as Indonesia's leading products in the CARICOM region faced lost opportunity market positions on average and CARICOM countries were included in the category as potential market developments. The United States, European Union, Brazil, China, South Korea, Japan, Dominica Republic, Colombia and Trinidad and Tobago and Singapore were identified as Indonesia's competitors in CARICOM. In terms of export determinants, real GDP and investment positive and significant effect on the export of Indonesia's superior products to CARICOM. Meanwhile, inflation and the real exchange rate together have a significant and negative effect in contrast to the economic distance which has a negative but insignificant effect on the volume of Indonesia's exports to the CARICOM region.